Black Religion and the Imagination of Matter in the Atlantic World - Noel, J. author. aut Link
XIII, 231 p.
Keywords: This book situates the study of Black Religion within the modern temporal and historical structures in the Atlantic World. It describes how black people and Black Religion made a phenomenological appearance in modernity simultaneously and were signified in the identity formation of whites and their religion.